2018
DOI: 10.1080/10691898.2018.1473061
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Association Between Precourse Metrics of Student Preparation and Student Performance in Introductory Statistics: Results from Early Data on Simulation-Based Inference vs. Nonsimulation-Based Inference

Abstract: The recent simulation-based inference (SBI) movement in algebra-based introductory statistics courses (Stat 101) has provided preliminary evidence of improved student conceptual understanding and retention. However, little is known about whether these positive effects are preferentially distributed across types of students entering the course. We consider how two metrics of Stat 101 student preparation (pre-course performance on concept inventory and math ACT score) may or may not be associated with end of cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…As discussed in Tintle et al (2018), the instrument showed good reliability (Cronbach's alpha > 0.65), construct validity (e.g., stronger item-total correlations post-course than pre-course), and good predictive validity (moderate correlations with external measures of quantitative understanding (e.g., ACT score, r = 0.39); associations with positive attitudes and post-test scores (r > 0.25 for 5 of 6 SATS subscales). Additional details on reliability and validity for a single year of this sample (2016-2017) are provided in Tintle et al (2018).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in Tintle et al (2018), the instrument showed good reliability (Cronbach's alpha > 0.65), construct validity (e.g., stronger item-total correlations post-course than pre-course), and good predictive validity (moderate correlations with external measures of quantitative understanding (e.g., ACT score, r = 0.39); associations with positive attitudes and post-test scores (r > 0.25 for 5 of 6 SATS subscales). Additional details on reliability and validity for a single year of this sample (2016-2017) are provided in Tintle et al (2018).…”
Section: Instrumentsmentioning
confidence: 99%
“…Additionally, recent evidence at single institutions (Tintle et al, 2018, see also Figure 4) has suggested that students entering the course with weaker quantitative backgrounds may be among those that benefit the most from SBI curricula. Further research is needed to explore this trend across a wide range of institutions to confirm the generalizability of these findings and potentially different best practices curricularly or pedagogically when working with these groups.…”
Section: Future Directionsmentioning
confidence: 99%
“…The next essential ingredient in our teaching cocktail is simulation‐based inference (SBI). In addition to Cobb [6], who states that there is “no excuse not to teach SBI,” there is increasing evidence that SBI can improve statistical understanding (eg, [16,28,46]).…”
Section: Simulation For 21st‐century Inferencementioning
confidence: 99%
“…Previously our research on the effectiveness of SBI curricula has focused on measures of student learning in introductory statistics courses comparing SBI to non-SBI courses using pre/post course measures of conceptual understanding. Evidence is mounting that this approach not only improves student understanding of statistical inference but also improves understanding of the investigative process as a whole (e.g., Chance et al, 2022;Tintle et al, 2011Tintle et al, , 2018. However, are there "optimal" ways of introducing "simulation-based inference" to these students?…”
Section: Introductionmentioning
confidence: 99%